Genomequest in teaching protein synthesis for grade 10 science: Game-based strategy - Carolyn T. Relacion; Lovely A. Verdijo; Vilma O. Dela Torre (JPBI (Jurnal Pendidikan Biologi Indonesia), 2025)
Challenges are inevitably present in every classroom, affecting teachers and students. Students are confronted with struggles in learning complex biology concepts that compel teachers to be resourceful and creative in providing positive learning environments, including the provision of effective learning materials that aid in the student’s mastery of learning competencies. This study was conducted to determine the effectiveness of the game-based strategy using the Genomequest in teaching protein synthesis. Quasi-experimental design was utilized specifically through pre-post testing in experimental and control groups and considering students’ level of satisfaction using the survey questionnaires. Results revealed that the board game utilized as an intervention was effective in learning protein synthesis. This was confirmed by the student’s level of satisfaction with their experiences. They enjoyed the collaborative activities included in the board game while learning the concept. Recommendations were made specifically on some of the parameters of the board game for more improved design and mechanics, for future implementation of the Genomequest in biology class, and considerations for future research.